Lightning surge analysis on a large scale grid-connected solar photovoltaic system - Zaini, Nur Hazirah; Ab Kadir, Mohd Zainal Abidin; Mohd Radzi, Mohd Amran; Izadi, Mahdi; Azis, Norhafiz; Ahmad, Nor Izzati; Mohd Nasir, Mohd Solehin (MDPI, 2017)
Solar photovoltaic (PV) farms currently play a vital role in the generation of electrical power in different countries, such as Malaysia, which is moving toward the use of renewable energy. Malaysia is one of the countries with abundant sunlight and thus can use solar PV farms as alternative sources for electricity generation. However, lightning strikes frequently occur in the country. Being installed in open and flat areas, solar PV farms, especially their electronic components, are at great risk of damage caused by lightning. In this paper, the effects of lightning currents with different peak currents and waveshapes on grid-connected solar PV farms were determined to approximate the level of transient effect that can damage solar PV modules, inverters and transformers. Depending on the location of the solar PV farm, engineer can obtain information on the peak current and median current of the site from the lightning location system (LLS) and utilise the results obtained in this study to appropriately assign an SPD to protect the solar panel, inverter and the main panel that connected to the grid. Therefore, the simulation results serve as the basis for controlling the effects of lightning strikes on electrical equipment and power grids where it provides proper justification on the ‘where to be installed’ and ‘what is the rating’ of the SPD. This judgment and decision will surely reduce the expensive cost of repair and replacement of electrical equipment damages due to the lightning.